Detection of Leptospires serogroups, Which Are Common Causes of Human Acute Leptospirosis in Guilan, Northern Iran - HR Honarmand; SS Eshraghi (Tehran University of Medical Sciences, 2011)
"nBackground: This study is performed to reveal most common species and subspecies of leptospires that are main causes of human leptospirosis in Guilan, Northern Province of Iran. "nMethods: We performed IgM-ELISA and MAT on 282 blood samples from patients who attended to 3 hospitals in the flat area of Guilan Province with clinical symptoms consisted with leptospirosis.  All specimens with titers ≥ 160 against at least one pathogenic strain in MAT and with titers ≥160 in IgM-ELISA were regarded confirmed positive cases indicative acute disease. For any confirmed positive cases, we determined the strains, which had the highest titer to determine the frequency of most common serovars and serogroups. "nResults: Seventy of 282 sera had titers ≥160 against at least one pathogenic strain in MAT and titers ≥ 160 in IgM-ELISA. We determined frequency of common causative serogroups which had highest titers in 70 positive cases and only cases which had high titers in MAT and in IgM-ELISA were selected which is a reliable criterion to detect acute disease and to determine causative serogroup."nConclusion: Nine serogroups including sejroe, grippotyphosa, mini, ictero haemorrhagiae, celledoni, autumnalis, cynopteri, pomona, and javanica were more responsible of acute leptospirosis in Guilan.